Comparison of Flowrate and Occlusion in a Vertical Infusion Pump and Horizontal Infusion Pump - Nur Hasanah Ahniar; Hendra Marwazi; Rismarini Yufita (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2020)
Infusion pump is a device used to enter fluid into the patient's body through a continuous. At present there are two types of infusion pumps namely vertical infusion pumps and horizontal infusion pumps. Both infusion pumps have different technologies. The aim of this study is to compare the performance results of the two infusion pumps. Infusion Pump is given 3 different liquid infusions, use 3 parameters flowrate setting (50 ml / h; 100 ml / h; 200 ml / h) and the data collection repeated for 5 times, with 3 minutes time for each parameter. The results of data collection will be tested using the normality test and difference test. Infusion Pump was calibrated first by using the Infusion Device Analyzer to check the condition of the tool. Based on the results of the T-test where the significant value is greater than 0.05, which means that the null hypothesis is accepted while the alternative hypothesis is rejected